GE_GERICHTE P/16453/2009 vom 1. Oktober 2012 - GE Cour de justice (2012)
DROIT D'ÊTRE ENTENDU; ACQUITTEMENT; INDEMNITÉ(EN GÉNÉRAL); DROIT TRANSITOIRE ; ASSISTANCE JUDICIAIRE | CST.29.2; CPP.3; CPP.429; CPP.135; RAJ.16; CPP-GE.379